(untitled) (Ágora de Heterodoxias, 2023)
When we communicate, are we really communicating? Communication as a mean to transmit our ideas, opinions, moods, emotions, among other messages, is a skill that we develop as human beings throughout our lives. While it is true that we are constantly communicating through language (verbal, body or written), this communication is not always intelligent and effective; consequently, a gap is created between what we want to express and the way in which the message reaches the other person or persons.In science communication, in this particular case of the social sciences, there are also gaps, and we experience multiple disagreements as challenges to the claim in this encounter. The direction in that communicational encounter with that other is impregnated with the need to prove, justify and sometimes make the explanation inexhaustible in order to achieve understanding.